Differential Uridyl-diphosphate-Glucuronosyl Transferase 1A enzymatic arsenal explains the specific cytotoxicity of resveratrol towards tumor colorectal cells. (December 2022) - Amintas, Samuel; Beaumont, Pauline; Dupin, Charles; Moranvillier, Isabelle; Lamrissi, Isabelle; Patel, Elie; Fernandez, Benjamin; Bibeyran, Alice; Boutin, Julian; Richard, Tristan; Krisa, Stéphanie; Moreau-Gaudry, François; et al.
Graphical abstract: Highlights: Resveratrol differential effect in healthy and cancer cells is poorly understood. UGT1A8/1A10 enzymes conjugate resveratrol into non-toxic metabolites in healthy intestinal cells. UGT1A gene downregulation results in resveratrol toxicity in CRC and healthy intestine cells. UGT1A gene expression is downregulated in patient's colorectal cancer tissues and metastases. Resveratrol leads to nucleotide imbalance uncoupling cell growth and proliferation in CRC cells. Abstract: Resveratrol belongs to the Bioactive Food Component (BFC) family. It seems admitted that its cytotoxic action impacts tumor cells and spares healthy cells, but the published proofs remain rare. We hypothesized that cells may differentially metabolize resveratrol and lead to different systemic impacts. For this, resveratrol metabolization was evaluated by ultra-high-performance liquid chromatography (UHPLC) coupled with diode array detection (DAD), and correlated with the expression of Uridyl-diphosphate-Glucuronosyl Transferase 1A ( UGT1A ) genes. The expression of UGT1A genes in human colorectal tissues was studied with RNAseq databases. Functional validation of UGT1A enzymes implication in resveratrol sensitivity of colorectal cells established by UGT1A expression modulation. As resveratrol impacts the S phase of the cell cycle, nucleotide metabolic balance was assessed. We found that resveratrol was more cytotoxic in cells with downregulation of UGTs, i.e. tumor cells. Conversely, overexpression of the UGT1A10 gene in an initial resveratrol-sensitive tumor cell line restored the metabolization accompanied by cytotoxicity diminution. Resveratrol affected intestinal sensitive tumor cell homeostasis with a cell growth/proliferation decoupling, cell-cycle modulation, and UXP/AXP nucleotide imbalance resulting in a global reduction of transcription and translation. This impact on global cell activity was restricted to tumor cells. This study improves resveratrol's general knowledge and explains how its antitumor action can spare non-tumor cells. It also paves the way to select colorectal tumors eligible for resveratrol treatment potentiation without additional toxicity to healthy digestive tissues.